CLUSTERING GEOGRAPHICAL CHARACTERISTICS ARCHIPELAGIC PROVINCE FOR MARINE TOURISM DEVELOPMENT - Setiawan, Firman
This research formulates the classification of geographical characteristics archipelagic province for marine tourism development. The geographical characteristics chosen are the water area, land area, number of islands, depth, tides, coastline, and rainfall conditions. The Principal Component Analysis (PCA) method is used for the simplification of variables that facilitate interpretation in the analysis of clusters with the PCA biplot. The results of this study are geographical characteristics that could explain and clustering the provincial, with 2 (two) cluster of 11 provinces indicating the acrchipelagic province that is very potentially for marine tourism development.